1356Translating urban health research in Bangkok: partnership framework for building capacity in monitoring liveability. (2nd September 2021) - Alderton, Amanda; Nitvimol, Kornsupha; Higgs, Carl; Butterworth, Iain; Correia, Joana; Davern, Melanie; Badland, Hannah
Abstract: Focus of Presentation: This poster outlines a partnership framework for developing a web-based liveability indicators monitoring system for Bangkok, Thailand, as a mechanism for translating urban health research into urban planning and policy. We reflect on our partnership with the Bangkok Metropolitan Administration, including its critical success factors and framing around the Sustainable Development Goals, and provide an overview of the capacity building program supporting the use of the indicators in practice. Findings: In total, 65 indicators were calculated for Bangkok and housed in a web-based urban liveability portal. A series of capacity building activities, including face-to-face meetings, webinars and online presentations, supported the use of these indicators in monitoring liveability. Numerous critical success factors were identified, such as having a bilingual liaison as well as two working groups within the Bangkok Metropolitan Administration. Conclusions/Implications: This partnership provides a framework for other cities seeking to translate urban health research and progress the Sustainable Development Goals through building capacity in monitoring liveability. Future international partnerships should seek to engage partners through a mix of face-to-face and online activities and develop project governance structures (e.g. bilingual project liaison) that enable the prioritisation of local knowledge. Key messages: This partnership provides a framework for translating urban health research into urban planning and policy, with relevance for other cities globally. It resulted in the mapping of 65 liveability indicators across Bangkok.